2015
DOI: 10.1111/ajad.12287
|View full text |Cite
|
Sign up to set email alerts
|

Social factors and readmission after inpatient detoxification in older alcohol‐dependent patients

Abstract: This study shows that most social factors are-unexpectedly-not associated with rehospitalization of older alcohol-dependent patients after detoxification. "Spending leisure time alone" warrants further study as a potentially modifiable predictor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These patients also yielded more previous admissions, comorbidities, and accidents involving poisoning, adverse drug reactions, or falls. A study from the Netherlands in this age group found that spending leisure time alone was associated with higher readmission rates (7).…”
Section: Introductionmentioning
confidence: 90%
“…These patients also yielded more previous admissions, comorbidities, and accidents involving poisoning, adverse drug reactions, or falls. A study from the Netherlands in this age group found that spending leisure time alone was associated with higher readmission rates (7).…”
Section: Introductionmentioning
confidence: 90%
“…The time‐frame for readmissions varied greatly from within 30 days of discharge [ 25 ] to within 2.5 years of discharge [ 65 ]. Other outcomes related to relapse include the use of a Maudsley Addiction Profile and author‐created questionnaire to determine factors related to relapse in one study [ 66 ] and measuring the effect of social factors on relapse in another [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary because withdrawal from alcohol (and other sedative-hypnotics) that is not medically managed may lead to autonomic instability, seizures, delirium, or death. Opioid withdrawal syndrome poses nearly no mortality risk but can be protracted with intense symptoms, and the risk from overdose is significant for patients who relapse after withdrawal because of loss of opioid tolerance (VA/DoD, 2015).…”
Section: Treatment and Outcomes Among Detoxification Inpatientsmentioning
confidence: 99%